Review of Key Technology and Latest Research Progress of Deflector Jet Servo Valve - Li, Jianying; Guo, Qi; Wang, Yaqian; Zhang, Xiaoqiu (Recent Patents on Engineering, 2025)
The deflector jet servo valve has the advantages of strong anti-pollution ability, high reliability and better dynamic performance, so it is widely used in aviation, military and other fields. The research on deflector jet servo valve theory and production is not yet mature. It is expected that through the collation and analysis of the existing data, the method of improving the performance of this kind of valve will be obtained, which will provide the basis for future research and development. By summarizing the research status of the static and dynamic characteristics, pre-stage optimization, mathematical modeling and other parts of the deflector jet servo valve, the technical points and development rules are obtained. By sorting out the relevant patent information in recent years, the vacancy in the patent analysis of the deflector jet servo valve is filled. Based on the summary of the research status of the deflector jet servo valve, combined with the summary of the research status of the deflector jet servo valve, it is pointed out that there are few studies on the performance of deflector jet servo valve under cavitation, noise and extreme temperature. These parameters are of great significance to improve the performance of servo valve, which will be an important research direction in the future. The research status and development trend of the deflector jet servo valve are summarized and analyzed, and various methods that can improve the performance of the servo valve are described, which is of great significance for the subsequent performance improvement and in-depth study of such valves.
Keywords: performance analysis